The evolution of wages in early modern Normandy (1600-1850) - Cédric Chambru; Paul Maneuvrier-Hervieu (University of Zurich, Department of Economics, 2021)
This paper presents new estimations of wages for Normandy between 1600 and 1850. We used a vast array of primary and secondary sources to assemble two new databases on wages and commodity prices to establish a new regional consumer price index (CPI) and twelve regional wage series. We posit that the sluggish demographic growth during the 18th century, and the resulting labour shortage, led to a convergence of wages across unskilled occupations and a relative catch-up with urban skilled construction labourers in the years preceding the French Revolution. We also provide tentative evidence suggesting that labourers in stable employment could have earned as much as their English counterparts during this period.
Keywords: J3; J4; I31; N33; 330; Prices; wages; casual employment; stable employment; Normandy